Implementasi Metode AHP Untuk Sistem Pendukung Keputusan Proses Kenaikan Jabatan Karyawan - Jeperson Hutahaean; Wily Julitawaty (SATESI: Jurnal Sains Teknologi dan Sistem Informasi, 2021)
Promotion or promotion is a transfer that increases the authority and responsibility of employees to higher positions within the organization so that the obligations, both status and income are greater. Almost all employees want to get a promotion. This research discusses finding the best solution to help take the decision to increase employee positions at PT. Prudential uses the Analitycal Hierarchy Process method to help determine the preferred priorities of various alternatives. This method was chosen because it is able to select the best candidates from a number of existing employees to occupy available positions based on predetermined criteria. Research is conducted by looking for weight values for each attribute, such as examples are aspects of intellectual capacity, aspects of work attitudes, and behavioral aspects, then carried out a perankingan process that will determine the optimal alternative, namely the promotion of employee positions. As a result of the application of the AHP method in this study, the value of the determination of the promotion of employee promotion 0 - 6 was declared unfit to be promoted and if the value is greater than 6, then the employee is declared worthy to be promoted to his position.